H6D Polymorphism in Macrophage-Inhibitory Cytokine–1 Gene Associated With Prostate Cancer - Lindmark, Fredrik; Zheng, S. Lilly; Wiklund, Fredrik; Bensen, Jeannette; Bälter, Katarina Augustsson; Chang, Baoli; Hedelin, Maria; Clark, Jonathan; Stattin, Pär; Meyers, Deborah A.; Adami, Hans-Olov; Isaacs, William; et al. (JNCI : Journal of the National Cancer Institute, 2004)
Background: Accumulating epidemiologic and molecular evidence suggest that inflammation is an important component in the etiology of prostate cancer. Macrophage-inhibitory cytokine–1 (MIC-1), a member of the transforming growth factor β superfamily, is thought to play an important role in inflammation by regulating macrophage activity. We examined whether sequence variants in the MIC-1 gene are associated with the risk of prostate cancer. Methods: The study population, a population-based case–control study in Sweden, consisted of 1383 prostate cancer case patients and 780 control subjects. From 94 of the control subjects, we constructed gene-specific haplotypes of MIC-1 and identified four haplotype-tagging single-nucleotide polymorphisms (SNPs): Exon1+25 (V9L), Exon1+142 (S48T), IVS1+1809, and Exon2+2423 (H6D). All study subjects were genotyped for the four SNPs, and conditional logistic regression analysis was used to estimate odds ratios (ORs) with 95% confidence intervals (CIs). Results: A statistically significant difference (P = .006) in genotype frequency was observed for the nonsynonymous change H6D (histidine to aspartic acid at position 6) between prostate cancer patients and control subjects. Carriers of the GC genotype, which results in the H6D change, experienced a lower risk of sporadic prostate cancer (OR = 0.80, 95% CI = 0.66 to 0.97) and of familial prostate cancer (OR = 0.61, 95% CI = 0.42 to 0.89) than the CC genotype carriers. In the study population, the proportion of prostate cancer cases attributable to the CC genotype was 7.2% for sporadic cancer and 19.2% for familial cancer. None of the other SNPs or haplotypes was associated with prostate cancer. Conclusion: This study shows an association between a nonsynonymous change (H6D) in the MIC-1 gene and prostate cancer. This finding supports the hypothesis that genetic variation in the inflammatory process contributes to prostate cancer susceptibility.